2015
DOI: 10.1111/hepr.12515
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiviral therapy for hepatitis C following treatment of hepatocellular carcinoma: survey findings of the Japanese Red Cross Liver Study Group

Abstract: Although complete prevention of HCC recurrence is difficult, the most important factor affecting first recurrence is the AFP level at 6 months after the conclusion of antiviral treatment. The survival rate improves dramatically if the hepatitis C virus is eliminated, but the most important factor for improving survival is absence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…From 858 unique results identified from our initial search strategy, the manuscripts of 45 potentially relevant abstracts were reviewed in full detail. Ten studies (all cohort studies) reporting on the association between SVR and outcomes in patients with HCV infections after local therapies for HCC were selected . HRs in two of these studies were obtained by correspondence with the authors .…”
Section: Resultsmentioning
confidence: 99%
“…From 858 unique results identified from our initial search strategy, the manuscripts of 45 potentially relevant abstracts were reviewed in full detail. Ten studies (all cohort studies) reporting on the association between SVR and outcomes in patients with HCV infections after local therapies for HCC were selected . HRs in two of these studies were obtained by correspondence with the authors .…”
Section: Resultsmentioning
confidence: 99%
“…Chronic hepatitis virus infection can lead to persistent hepatic inflammation and liver fibrosis, which may further result in a higher tumor recurrence rate and inferior liver function reserve. 33 As it was suggested by several authors that antiviral therapies after hepatectomy may influence the recurrence rate as well as the OS of patients with HCC, [33][34][35][36] it would be interesting to evaluate the prognostic value of postoperative antiviral therapies in our cohort. To our regret, due to the retrospective nature of the study, we failed to obtain the detailed data regarding antiviral therapy following hepatectomy in these patients; this factor will be taken into consideration in our future study design.…”
Section: Discussionmentioning
confidence: 99%
“…This nationwide observational multicenter study was undertaken by the Japanese Red Cross Liver Study Group, including 24 centers of Japanese Red Cross Hospitals. Previously, we reported that the overall SVR rate for GT2 patients treated with SOF + RBV was 96.8% in a multicenter cohort .…”
Section: Methodsmentioning
confidence: 99%